Reflexivity and the challenges of ethnographic film - Mhiripiri, Nhamo A. (Taylor & Francis (Routledge), 2016)
For over three decades now, Jay Ruby has championed the rethinking of the theory, production, and ethics of visual anthropology and ethnographic filmmaking. He has always challenged both academics and filmmakers to analyze critically what is and what is not ethnographic film, and has argued how reflexivity can be used to improve the quality and content of this film genre. His latest book is therefore a timely extensive updating of previously published ideas on the field. He has been consistent in attempting to theorize the anthropology of visual communication as well as to give the broad field the recognition it deserves in academia. My reading of Ruby is therefore in terms of the popularization of the notion and practice of reflexivity and its application to specific films. It is also pertinent to see how filmmakers have taken up reflexivity.